A Jasmonic Acid–Related Mechanism Affects ARGONAUTE5 Expression and Antiviral Defense Against Potato Virus X in Arabidopsis thaliana - Guilherme Silva-Martins; Charles Roussin-Léveillée; Ayooluwa Bolaji; Varusha Pillay Veerapen; Peter Moffett (Molecular Plant-Microbe Interactions, 2023)
During virus infection, Argonaute (AGO) proteins bind to Dicer-produced virus small interfering RNAs and target viral RNA based on sequence complementarity, thereby limiting virus proliferation. The Arabidopsis AGO2 protein is important for resistance to multiple viruses, including potato virus X (PVX). In addition, AGO5 is important in systemic defense against PVX. Normally AGO5 is expressed only in reproductive tissues, and its induction by virus infection is thought to be important for its participation in antiviral defense. However, it is unclear what mechanisms induce AGO5 expression in response to virus infection. Here, we show that dde2-2, a mutant compromised in jasmonic acid (JA) biosynthesis, displays constitutive upregulation of AGO5. This mutant also showed increased resistance to PVX and this resistance was dependent on a functional AGO5 gene. Furthermore, methyl jasmonate treatment ablated AGO5 expression in leaves during virus infection and resulted in increased susceptibility to virus. Our results further support a role for AGO5 in antiviral RNA silencing and a negative regulation by JA, a plant hormone associated with defense against plant-feeding arthropods, which are often the vectors of plant viruses. [Graphic: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.